Lighting for animation the art of visual storytelling - Katatikarn, Jasmine; Tanzillo, Michael (CRC Press, Taylor & Francis Group, A Focal Press Book, 2017)
"Lightning for animation is designed with one goal in mind--to make you a better artist. Over the course of the book, Jasmine Katatikarn and Michael Tanzillo (Senior LIghting TDs, Blue Sky Studios) will train your eye to analyze your work more critically, and teach you approaches and techniques to improve your craft. Focusing on the main philosophies and core concepts utilized by industry professionals, this books builds the foundation for a successful career as a lighting artist in visual effects and computer animation." -- Provided by publisher